2013
DOI: 10.1021/ac401665u
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Microfluidic Device for Monitoring Changes in Nitric Oxide Production in Single T-Lymphocyte (Jurkat) Cells

Abstract: A considerable amount of attention has been focused on the analysis of single cells in an effort to better understand cell heterogeneity in cancer and neurodegenerative diseases. Although microfluidic devices have several advantages for single cell analysis, few papers have actually demonstrated the ability of these devices to monitor chemical changes in perturbed biological systems. In this paper, a new microfluidic channel manifold is described that integrates cell transport, lysis, injection, electrophoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 58 publications
(129 reference statements)
2
40
0
1
Order By: Relevance
“…In most instances, the beneficial effects of Car treatment were related to its generally ascribed antioxidant activity [31], which involves a capacity to decrease both ROS and RNS in different experimental models [32, 33]. In agreement with these and other studies, our experiments with cultured murine RAW 264.7 macrophages, using ME-LIF to detect the stable fluorescent NO adduct in cell lysates [27, 34], confirmed that Car decreases NO concentration in stimulated cells in a dose-dependent manner (Fig. 1 and Online Resource 1).…”
Section: Discussionsupporting
confidence: 70%
“…In most instances, the beneficial effects of Car treatment were related to its generally ascribed antioxidant activity [31], which involves a capacity to decrease both ROS and RNS in different experimental models [32, 33]. In agreement with these and other studies, our experiments with cultured murine RAW 264.7 macrophages, using ME-LIF to detect the stable fluorescent NO adduct in cell lysates [27, 34], confirmed that Car decreases NO concentration in stimulated cells in a dose-dependent manner (Fig. 1 and Online Resource 1).…”
Section: Discussionsupporting
confidence: 70%
“…We have already reported a single cell chemical cytommetric device for NO detection from Jurkat cells using a NO-selective fluorophore. 29 The ultimate goal is to use ME-EC to measure multiple redox-active species in a single cell as an indication of nitrosative stress.…”
Section: Resultsmentioning
confidence: 99%
“…PDMS electrophoresis microchips were fabricated by soft lithography using a high‐relief master previously defined in silicon wafer as described elsewhere . Briefly, PDMS monomer and the curing agent were mixed at a ratio of 10:1 m/m, poured then on the master, and kept at 70ºC during 30 min.…”
Section: Methodsmentioning
confidence: 99%